Living with the Liyan: Ideological Interpretation of Deuteronomy 25:17-19 from the Perspective of the Other - Souhaly, Fitria; Tuasela, Juliana A (Program Pascasarjana UKIM, 2025)
Living together in diversity in Indonesia is still a problem that is sometimes not noticed and can trigger riots regardless of race, class or religion. The same thing is also found in Deuteronomy 25:17-19 which shows the relationship betweenAmalek and Israel as a nation fullofwar, sothat ifnot interpretedcritically it cancauseadestructive attitude towardsevery people who live side by side with the other. This article aims to interpret using ideological criticism. The ideological criticism attempts to find the author's meaning and the reader's ideology which are included in the interpretation system. The law of Deuteronomy 25:17-19 is an ideology of resistance to the other, so that there is a dominant mode that makesAmalek a representation of the indigenous people who are specifically described by D source’s as having power in terms of religion, economy and politics. Therefore, the ideology of liberation as a counter ideology to free people from the power of the elite. The ideology of GOD's universal love for all nations is a counter ideology to YHWH's theology of liberation which does not limit itself to every nation. This understanding gives birth to an awareness of people who live in diversity not to act militantly/aggressively to achievetheinterests of individuals or certain communities. Rather, it is important to have an awarenessoflifethatcancreateanattitudeof mutualacceptance toward the other and living in an attitude of tolerance